(untitled) (Research, Society and Development, 2022)
Considering the fragmentation of knowledge and the underutilization of Digital Information and Communication Technologies (DICTs) as relevant problems in the training of graduates, the present research aims to analyze how the understanding that graduates of a Public Institution of Higher Education (PIHE) present on teaching is transformed when they develop Educational Digital Authorial Materials (MADE) in the face of a teaching methodological context based on the theoretical precepts of meaningful learning. The methodology is based on a Case Study. The unit of analysis is composed of 34 undergraduates who took the Technoteaching discipline in 2019, forming 2 Cases. The research is divided into three stages: planning, data collection, and analysis. In the first, the protocols and instruments to be used in the other stages are prepared. In the second, data collection is carried out in 3 phases: the survey questionnaire, the post-MADE questionnaire, and the evaluation questionnaire. In the third, the interpretative data analysis is carried out based on methodological triangulation of the data, with the aid of Discursive Textual Analysis and Described Statistics, making the inference process better founded. Two categories are defined: teaching as transmission and teaching as innovation. It was found that working with MADEs caused momentary changes in what undergraduates think about education. In addition, there was an expansion in the use of terms that connect the concept of teaching to a model based on the production of conceptual changes.